Postmodern marketing as a framework for developing marketing ethics - an applied study in a sample of international companies operating in the United States of America - علاء فرحان طالب،,; عبد الحسين حسن حبيب،,; ليلى محسن الحكيم, (Iraqi Journal for Administrative Sciences, 2025)
By reviewing the literature of the marketing department turned out that the development of marketing ethics is an important mechanism for the company can be achieved competitive advantage in light of a rapidly changing business environment. With the transformation of the world from modernity to postmodernity at the beginning of the second half of the twentieth century changed with corporate thinking and way of dealing with customers and took up the votes to claim certainly on moral values in these companies and how to communicate effectively and use friendly relations with customers and with the environment at the same time. Was the objective of the study on the role of marketing postmodern ethics in the development of marketing. So began the study of the problem expressed in a number of questions of intellectual and practical, Aimed at answering them through philosophy and theoretical implications for intellectual variables addressed by the study, which is (Marketing postmodern - Marketing Ethics). And then diagnose the level of importance and impact and the possibility of their application in companies. This study was applied to a group of international companies operating in the United States through a sample composed of (109), a member of senior management positions where The measuring instrument is designed to collect the necessary data.